The empty chair - Deaver, Jeffery (New York : Simon, 2000)
A disagreement over the guilt of a teenager wanted for murder pits the noted criminalist Lincoln Rhyme against his young protegee Amelia Sachs.
10-A.
Keywords: Rhyme, Lincoln (Fictitious character) -- Fiction; Forensic pathologists -- Fiction; Physically handicapped -- Fiction; Mystery fiction; North Carolina -- Fiction